Associations of emotional/behavioral problems with accelerometer-measured sedentary behavior, physical activity and step counts in children with autism spectrum disorder - Li, Hailin; Shi, Bijun; Wang, Xin; Cao, Muqing; Chen, Jiajie; Liu, Siyu; Zhan, Xiaoling; Jin, Chengkai; Gui, Zhaohuan; Jing, Jin; Zhu, Yanna (Frontiers in Public Health, 2022)
Background The evidence for associations of emotional/behavioral status with sedentary behavior (SB), physical activity (PA) and step counts is scarce in children with autism spectrum disorder (ASD). Also, ASD-related deficiencies may affect actual levels of PA. We aimed to describe accelerometer-measured SB, PA and step counts in children with ASD, and to examine the associations of emotional/behavioral problems with SB, PA and step counts after assessing associations between accelerometer-measured SB, PA and step counts and ASD-related deficiencies. Methods A total of 93 ASD children, aged 6–9 years, were recruited from the Center for Child and Adolescent Psychology and Behavioral Development of Sun Yat-sen University in Guangzhou, China. Participants wore an accelerometer for seven consecutive days. Of the original 93, 78 participants' accelerometer-measured valid PA were obtained, and the data were shown as time spent in SB, light, moderate, moderate-to-vigorous and vigorous PA, and step counts. Participants' emotional/behavioral problems were assessed via the Strengths and Difficulties Questionnaire (SDQ), and anxiety symptoms were evaluated by the Screen for Child Anxiety Related Emotional Disorders (SCARED). ASD-associated deficiencies include restricted repetitive behaviors (Repetitive Behavior Scale-Revised), poor social competence (Social Responsiveness Scale Second Edition) and motor development restrictions (Developmental Coordination Disorder Questionnaire). Results Of the 78 participants, daily vigorous PA (VPA) and moderate-to-vigorous PA (MVPA) averaged 15.62 and 51.95 min, respectively. After adjustment for covariates, SDQ emotional symptoms (β = −0.060, p = 0.028) were inversely associated with the average daily minutes in VPA. Meanwhile, SDQ emotional symptoms (β = −0.033, p = 0.016) were inversely associated with the average daily MVPA minutes in the crude model. After adjustment for covariates, SCARED somatic/panic (β = −0.007, p = 0.040) and generalized anxiety (β = −0.025, p = 0.014) were negatively associated with the average daily VPA minutes; SCARED total anxiety (β = −0.006, p = 0.029) was conversely associated with daily MVPA duration. After adjustment for covariates, no significant associations between accelerometer-measured SB, PA and step counts and ASD-related deficiencies were found (p > 0.05). Conclusions Accelerometer-measured SB, PA and step counts showed no associations with ASD-related deficiencies. On this basis, we further found that the emotional symptoms were inversely associated with VPA and MVPA. These results emphasize the importance of VPA and MVPA in children with ASD. The longitudinally investigations on the directionality of these associations between emotional symptoms with VPA and MVPA are needed in the future.